2017
DOI: 10.1371/journal.pone.0177930
|View full text |Cite|
|
Sign up to set email alerts
|

High prevalence of elevated blood lead levels in both rural and urban Iowa newborns: Spatial patterns and area-level covariates

Abstract: Lead in maternal blood can cross the placenta and result in elevated blood lead levels in newborns, potentially producing negative effects on neurocognitive function, particularly if combined with childhood lead exposure. Little research exists, however, into the burden of elevated blood lead levels in newborns, or the places and populations in which elevated lead levels are observed in newborns, particularly in rural settings. Using ~2300 dried bloods spots collected within 1–3 days of birth among Iowa newbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 80 publications
1
13
1
Order By: Relevance
“…These findings are in disagreement with those published by Meza-Montenegro (2013) [ 45 ].The reason for this difference may be due to differences in the SES of each country’s agricultural area. However, recent study has shown that lead exposure in rural areas is high as in our study [ 46 ].…”
Section: Discussioncontrasting
confidence: 63%
“…These findings are in disagreement with those published by Meza-Montenegro (2013) [ 45 ].The reason for this difference may be due to differences in the SES of each country’s agricultural area. However, recent study has shown that lead exposure in rural areas is high as in our study [ 46 ].…”
Section: Discussioncontrasting
confidence: 63%
“…In this item,contamination generally is greater in urban than rural areas where there is no specific or identified point sources, though, our finding showed that no differences in blood lead levels are observed between urban and rural maternal residence. A detailed research [21] confirm our result and suggest that rural populationsare at as great of risk of elevated blood lead levels as are urban populations.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, we only examined individual-level characteristics and not ecological-level variables such as the percent Black population. Other geographical covariates in the NHANES such as differing US regions or urban vs. rural setting were also not examined, although authors have reported such significant variations in childhood blood Pb nationally and between different states [82,[105][106][107][108][109].…”
Section: Study Limitations and Interpretationmentioning
confidence: 99%